How far have we explored fungi to fight cancer?. (November 2022) - How, Chee Wun; Ong, Yong Sze; Low, Sze Shin; Pandey, Ashok; Show, Pau Loke; Foo, Jhi Biau
Abstract: The use of fungal cultures have been well documented in human history. Although its used in healthcare, like penicillin and statins, have saved countless of lives, but there is still no fungal products that are specifically indicated for cancers. Research into fungal-derived materials to curb cancers in the recent decades have made a considerable progress in terms of drug delivery vehicles, anticancer active ingredients and cancer immunotherapy. Various parts of the organisms have successfully been exploited to achieve specific tasks. Apart from the identification of novel anticancer compound from fungi, its native capsular structure can also be used as drug cargo to achieve higher oral bioavailability. This review summarises the anticancer potential of fungal-derived materials, highlighting the role of capsular polysaccharides, proteins, and other structures in variety of innovative utilities to fit the current pharmaceutical technology. Many bioactive compounds isolated from fungi have also been formulated into nanoparticles to achieve greater anticancer activity. The progress of fungal compounds and their analogues in clinical trials is also highlighted. In addition, the potential of various fungal species to be developed for anticancer immunotherapy are also discussed.